FOREST Unbiased Galactic Plane Imaging Survey with the Nobeyama 45 m telescope (FUGIN). V. Dense gas mass fraction of molecular gas in the Galactic plane. (17th April 2019) - Torii, Kazufumi; Fujita, Shinji; Nishimura, Atsushi; Tokuda, Kazuki; Kohno, Mikito; Tachihara, Kengo; Inutsuka, Shu-ichiro; Matsuo, Mitsuhiro; Kuriki, Mika; Tsuda, Yuya; Minamidani, Tetsuhiro; Umemoto, Tomofumi; et al.
Abstract: Recent observations of the nearby Galactic molecular clouds indicate that the dense gas in molecular clouds has quasi-universal properties on star formation, and observational studies of extra-galaxies have shown a galactic-scale correlation between the star formation rate (SFR) and the surface density of molecular gas. To reach a comprehensive understanding of both properties, it is important to quantify the fractional mass of dense gas in molecular clouds, f DG . In particular, for the Milky Way (MW) there are no previous studies resolving f DG disk over a scale of several kpc. In this study, f DG was measured over 5 kpc in the first quadrant of the MW, based on the CO J = 1–0 data in l = 10°–50° obtained as part of the FOREST Unbiased Galactic plane Imaging survey with the Nobeyama 45 m telescope (FUGIN) project. The total molecular mass was measured using 12 CO, and the dense gas mass was estimated using C 18 O. The fractional masses, including f DG, in the region within ±30% of the distances to the tangential points of the Galactic rotation (e.g., the Galactic Bar, Far-3 kpc Arm, Norma Arm, Scutum Arm, Sagittarius Arm, and inter-arm regions) were measured. As a result, an averaged f DG of 2.9^+2.6_-2.6 % was obtained for the entirety of the target region. This low value suggests that dense gas formation is the primary factor in inefficient star formation in galaxies. It was also found that f DG shows large variations depending on the structures in the MW disk. In the Galactic arms, f DG was estimated to be ∼4%–5%, while in the bar and inter-arm regions it was as small as ∼0.1%–0.4%. These results indicate that the formation/destruction processes of the dense gas and their timescales are different for different regions in the MW, leading to differences in Star formation efficiencies.